The Unbelieved and Historians, Part I: A Challenge. Issue 12 (December 2016) - Clossey, Luke; Jackson, Kyle; Marriott, Brandon; Redden, Andrew; Vélez, Karin
Abstract: In 1855, Thakur led a rebellion of the tribal Santals against the British in eastern India. Some historians refused to admit Thakur's involvement in the event because of a three‐century‐old prejudice against giving supernatural beings agency when we write history. In Provincializing Europe, Dipesh Chakrabarty argues that historians must "anthropologize" such beliefs rather than take them seriously. Taking a cue from their less‐than‐marginal place in scholarship today, we call supernatural beings the "Unbelieved" and the explicit or implicit denial of them "Dogmatic Secularism." We argue that objective historians should not discount, in advance, evidence that points to the existence or involvement of the Unbelieved in history; instead, we should cultivate a sceptical attitude towards all sources. In this, the first half of a two‐part essay, we trace the boundaries of this epistemological problem in the scholarship about the Santal Rebellion and beyond.